Covid-19 mortality in children and adolescents in Mexico - Dalia Stern; Eduardo Arias-de la Garza; María Teresa García-Romero; Martin Lajous (Instituto Nacional de Salud Pública, 2022)
Objective. To estimate Covid-19 and pre-pandemic low respiratory infection (LRI) mortality in children and adolescents in Mexico. Materials and methods. We estimated the percentage of total mortality attributable to Covid-19 (95% confidence intervals; 95%CI) and made the corresponding estimates for pre-pandemic LRI mortality. Results. In 2019, LRIs represented 8.6% (95%CI 8.3, 8.9) of deaths in children aged 0-9 years, and 2.0% (95%CI 1.8, 2.3) in those aged 10-19 years. In 2020, the corresponding estimates for Covid-19 were 4.4% (95%CI 4.1, 4.6) and 3.7% (95%CI 3.4, 4.1). Conclusions. Relative to LRI, Covid-19 may be exerting a considerable mortality burden, particularly in older children and adolescents.